1970
DOI: 10.1128/jvi.6.4.519-533.1970
|View full text |Cite
|
Sign up to set email alerts
|

Interruption by Rifampin of an Early Stage in Vaccinia Virus Morphogenesis: Accumulation of Membranes Which Are Precursors of Virus Envelopes

Abstract: Assembly of vaccinia virus envelopes and immature vaccinia particles was interrupted in HeLa cells treated with rifampin ( rifampicin ). The primary action of rifampin on vaccinia morphogenesis appeared to occur during the stage of envelope formation. When envelopes and immature particles were already present, maturation could continue, even in the presence of rifampin. It was demonstrated that the trilaminar membranes of irregular contour which accumulate in the presence of rifampin ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0

Year Published

1971
1971
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(82 citation statements)
references
References 36 publications
4
78
0
Order By: Relevance
“…They concluded that the spike layer stabilized the crescent membrane and imposed a curvature upon it, and they stressed that when the spikes were prevented from associating with the developing IVs by the drug Rifampicin, the IV membrane became floppy and tended to close up upon itself. This latter observation has been confirmed many times, and has been highlighted by many demonstrations of just how promptly crescent formation resumes upon washout of Rifampicin-again, with the crescents invariably displaying the spike layer as soon as they begin to reform (Moss et al, 1969;Grimley et al, 1970;Nagayama et al, 1970;Pennington et al, 1970;Follett and Pennington, 1971;Grimley and Moss, 1971;Moss et al, 1971;Pennington and Follett, 1971). In a subsequent report, we will use the imaging techniques introduced here to confirm that the external lattice is indeed D13L, that D13L is indeed a trimer, and that D13L is indeed capable of polymerizing into a continuous, self-supporting honeycomb (unpublished data).…”
Section: Discussionmentioning
confidence: 68%
“…They concluded that the spike layer stabilized the crescent membrane and imposed a curvature upon it, and they stressed that when the spikes were prevented from associating with the developing IVs by the drug Rifampicin, the IV membrane became floppy and tended to close up upon itself. This latter observation has been confirmed many times, and has been highlighted by many demonstrations of just how promptly crescent formation resumes upon washout of Rifampicin-again, with the crescents invariably displaying the spike layer as soon as they begin to reform (Moss et al, 1969;Grimley et al, 1970;Nagayama et al, 1970;Pennington et al, 1970;Follett and Pennington, 1971;Grimley and Moss, 1971;Moss et al, 1971;Pennington and Follett, 1971). In a subsequent report, we will use the imaging techniques introduced here to confirm that the external lattice is indeed D13L, that D13L is indeed a trimer, and that D13L is indeed capable of polymerizing into a continuous, self-supporting honeycomb (unpublished data).…”
Section: Discussionmentioning
confidence: 68%
“…Important and still unresolved issues about VV assembly are how the full complement of proteins become wrapped by the viral membrane to generate individual spherical IVs and how the genomic DNA is incorporated into these particles. Several studies suggested that the viral DNA packed into a nucleoprotein complex is taken up before the IVs are completely sealed (13,18,28,31).…”
Section: Discussionmentioning
confidence: 99%
“…These images are not frequently seen by electron microscopy during a normal infection, suggesting that this would be a very efficient and fast process. However, certain abortive infections in which VV assembly is blocked result in the accumulation of large cytoplasmic DNA crystalloids that have the appearance of densely packed, ordered fibrils (8,18,31,36,52). Such DNA crystalloids were also seen in cells infected with a conditional mutant that inducibly expresses the A32 gene and which has been described as a DNA packaging mutant (4).…”
Section: Suspensions Of Purified Wr Vv and Vvinda10lmentioning
confidence: 99%
See 1 more Smart Citation
“…To further examine the importance of fatty acid biosynthesis to viral assembly, we performed infections in the presence of rifampicin; the reversible inhibitor rifampicin prevents the interaction of the viral proteins D13 and A17, thereby preventing the assembly of immature virions [31][32][33][34]. In the presence of rif, DNA replication and the full profile of protein expression proceed normally, but morphogenesis arrests at an early stage [35].…”
Section: Viral Assembly Is Inhibited By Tofa and C75mentioning
confidence: 99%